Biographic Context in V. V. Nabokov’s Novels “Glory” and “Transparent Things” - E. G. Nikolayeva (Научный диалог)
Novels by V. Nabokov “Glory” and “Transparent Things” are considered from the point of view of representation of biographical material in them. The references in these novels to the works of Russian and foreign literature, to the biographies of writers and poets (“biographical plot”) speak not only about Nabokov’s cultivation of a new plot on the basis of the combinatorics of borrowed plots and their elements, but also about the meta-literary discussion of these plots, biographies and creative experience of predecessors. The article compares the features of the narrative of A. J. Cronin’s novel “Adventures in Two Worlds” and Nabokov’s artistic principles allowing to combine biographical facts and fiction. Thus, Nabokov’s lineage is considered. It became “plot-genic” - it influenced the emergence of plots of “The Enchanter”, “Lolita” and in collapsed form of “The Gift” and “Transparent Things.” The relationship between the Moliere and Armande Bejart is compared with the line “Armande - Hugh Person” in “Transparent Things.” Links between the novels by V. V. Nabokov “Glory” and “Transparent Things” with the works and biography of Lermontov are traced. In particular, attention is paid to the figures of Lermontov’s fellow students - D. V. Peterson and Ya. R. Gruzinov.